2013
DOI: 10.3322/caac.21218
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer and circadian disruption from electric lighting in the modern world

Abstract: Breast cancer is the leading cause of cancer death among women worldwide and there is only limited explanation of why. Risk is highest in the most industrialized countries but also rising rapidly in the developing world. Known risk factors account for only a portion of the incidence in the high risk populations, and there has been considerable speculation, and many false leads, on other possibly major determinants of risk such as dietary fat. A hallmark of industrialization is the increasing use of electricity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
207
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(212 citation statements)
references
References 149 publications
3
207
0
2
Order By: Relevance
“…6 In addition, candle-light-style OLEDs emitting yellowish orange light have been demonstrated to be a physiologically friendly light at night. 26,27 Therefore, devices A-C are physiologically friendly light due to their relatively low intensities of blue emission.…”
Section: Resultsmentioning
confidence: 99%
“…6 In addition, candle-light-style OLEDs emitting yellowish orange light have been demonstrated to be a physiologically friendly light at night. 26,27 Therefore, devices A-C are physiologically friendly light due to their relatively low intensities of blue emission.…”
Section: Resultsmentioning
confidence: 99%
“…RNF115 is another ubiquitin E3 ligase that is strongly associated with increased tumor growth, particularly in response to estrogen (43). Many studies have found significant correlations between disrupted circadian rhythms and increased risk for certain cancers, including breast cancer (44). Ubiquitination regulates the stability of core clock proteins; thus, it is possible that this protein interacts with core circadian proteins to regulate rhythms in cell growth and differentiation (45).…”
Section: Discussionmentioning
confidence: 99%
“…As a disruption of light cycles increases the risk of breast cancer (13,47,48), it is plausible that melatonin and KiSS1 may exhibit similar expression patterns in breast cancer. Melatonin has been revealed to regulate circadian rhythms by inhibiting KiSS1 expression in the brain of rodents (27).…”
Section: Discussionmentioning
confidence: 99%